Rancang Bangun dan Uji Kinerja Mesin Pengolah Slurry Limbah Biogas Menjadi Pupuk Kompos Menggunakan Sistem Pemanas Gas LPG - Timotius Anggit Kristiawan; Trio Setiyawan; Iman Mujiarto; Atikah Ayu Janitra; Muhammad Ghani Ardi Kurniawan; Rafiq Afrizal Bastian (Politeknik Negeri Semarang, 2026)
Slurry generated from biogas production is commonly treated using natural drying methods, which require 30–40 days and intensive manual handling, making the process inefficient for practical applications. This study aims to design and evaluate the performance of a slurry drying machine utilizing LPG as a heat source with a capacity of 30 kg. The research methodology includes mechanical design, fabrication, and experimental performance testing. The developed system integrates a mechanical pressing unit, a rotating mixing drum, and a controlled LPG heating system driven by a 0.5 HP electric motor. Experimental results show that the machine is capable of reducing slurry mass by approximately 50% within 150 minutes at an operating temperature of 65–70 °C. The highest drying rate occurred during the first 30 minutes, indicating rapid moisture removal in the initial stage. Compared to conventional solar drying, the proposed system significantly reduces processing time while improving drying consistency. The developed machine demonstrates potential as an efficient and practical solution for converting biogas slurry into value-added organic fertilizer, particularly for small to medium-scale farming applications.